SPK Recommendations for Selection of Candidates for Structural Officers Using the Profile Matching Method - Jannah, aulia (Al'Adzkiya, 2021)
Through the State Civil Apparatus Law, the Government is making efforts to reduce nepotism by creating an open competition system among civil servants in the process of filling positions. The Tarakan Regional Civil Service Agency (BKD) already has an employee database and a decision support system that can combine the available databases with assessment models to obtain candidate profiles that match the vacant position profiles needed to support more objective performance. The application of the profile matching method in this decision-making system is expected to assist in the process of recommending candidates for structural officials within the Tarakan City Government according to the capabilities of the fields required in a position. From the results of the study it was concluded that changes in candidate profile values, and the number of sub-criteria used for position criteria, can affect the closeness of candidates to available positions and the use of the profile matching method for cases where the highest score is the best value requires that the ideal value used is the highest score. maximum so that there are no expectations that exceed the ideal value.Keywords— Decision Making, System Profile Matching, City of Tarakan